2008
DOI: 10.1080/13625180701577114
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of contraception among Greek female medical students

Abstract: Much more time should be spent in teaching contraception in the Greek medical schools to ensure the delivery of adequate family planning guidance by future practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
5
7
0
2
Order By: Relevance
“…In total, 84.2% of the students were using condoms (alone, in combination with OC, in alternation or together with coitus interruptus, and in alternation or together with coitus interruptus or diaphragm). These findings are in agreement with previous reports on university students from Greece, 6,7 Spain and Portugal, 10 the United States, 11,12 and Japan. 13 In contrast, a recent study from Finland reported that less than one third of female university students use condoms.…”
Section: Contraceptive Use In Greek Dental Students 389supporting
confidence: 95%
See 2 more Smart Citations
“…In total, 84.2% of the students were using condoms (alone, in combination with OC, in alternation or together with coitus interruptus, and in alternation or together with coitus interruptus or diaphragm). These findings are in agreement with previous reports on university students from Greece, 6,7 Spain and Portugal, 10 the United States, 11,12 and Japan. 13 In contrast, a recent study from Finland reported that less than one third of female university students use condoms.…”
Section: Contraceptive Use In Greek Dental Students 389supporting
confidence: 95%
“…First, none of the students had had an abortion, in agreement with previous studies in Greek university students. 6,7 Similar surveys in other European countries and in Central America also suggested a low rate of abortions among university students. [20][21][22] These findings should be interpreted with caution, however, because students might not want to disclose such information even anonymously.…”
Section: Contraceptive Use In Greek Dental Students 389mentioning
confidence: 53%
See 1 more Smart Citation
“…9 Interestingly, the use of oral contraceptives seems to be rather low in Greece. 36 Taken together, the findings of the present study suggest that, in recent years, there is a rather favorable pattern regarding time trends of cervical cancer mortality in Greece. Still, primary and secondary preventive measures are needed, namely, a higher level of coverage of the female population with novel human papillomavirus vaccines and implementation of organized cytological screening.…”
Section: Discussionsupporting
confidence: 72%
“…The non-use of the condom is frequently associated with the assumption that condoms reduce sexual pleasure, or that partners will not approve of condom use, or the lack of discussion with partners about condoms 10 . Factors associated with inconsistent condom use include negative attitudes towards condoms prevailing in the community, a low level of education and economic asymmetries between partners [11][12][13] . Several community-based student surveys suggest that when teenagers talk with their parents about sex, they report greater contraceptive use, including use of the condom [14][15][16] .…”
mentioning
confidence: 99%